Polystyrene microplastics protect lettuce (Lactuca sativa) from the hazardous effects of Cu(OH)2 nanopesticides - Yan, Guanjie; Sun, YongHao; Yang, Liting; Zhang, Yao; Zhang, Weicheng (Frontiers in Plant Science, 2022)
Copper-based nanopesticides are released into the environment during foliar spray application, and they could, on their own or in combination with microplastics (MPs), pose threats to environmental safety and human health. In this study, Cu(OH)2 nanowires greatly decreased the vigour of lettuce seeds (p < 0.01) and the root length of lettuce seedlings (p < 0.01) and significantly altered the lettuce antioxidant defence system and MDA content (p < 0.05). Released Cu2+ played a critical role in the toxicity mechanism of Cu(OH)2 nanowires in lettuce seedlings, as evidenced by the substantial accumulation of Cu in the seedling roots (p < 0.01) rather than in the leaves. Polystyrene (PS) MPs (1 mg/L) stimulated lettuce seedling growth, as shown by the (highly) significant increase in root and leaf length and in the seed vigour index (p < 0.01 or 0.05). Notably, PS MPs (1 mg/L) neutralized the hazardous effects of 1 mg/L Cu(OH)2 nanowire treatment on lettuce growth, as reflected by the vitality and root length of the seedlings returning to normal levels. The PS MPs (1 mg/L) absorbed on middle root surfaces and strongly hindered Cu accumulation in lettuce roots, which was the predominant mechanism by which PS MPs suppressed the hazardous effects of the Cu(OH)2 nanowires. This study strengthens the understanding of the toxicity and toxicity mechanisms of Cu(OH)2 nanowires with or without PS MPs in the environment.